Cullin-3 and Regulatory Biomolecules Profiling in Vitiligo: Integrated Docking, Clinical, and In Silico Insights - Hidi A. A. Abdellatif; Mohamed Azab; Eman Hassan El-Sayed; Rwan M. M. M. Halim; Ahmad J. Milebary; Dhaifallah A. Alenizi; Manal S. Fawzy; Noha M. Abd El-Fadeal (Biomolecules)
Background: Vitiligo, a chronic depigmentation disorder driven by oxidative stress and immune dysregulation, remains poorly understood mechanistically. The Keap1/NRF2/ARE pathway is critical for melanocyte protection against oxidative damage; however, the role of Cullin-3 (CUL3), a scaffold for E3 ubiquitin ligases that regulate NRF2 degradation, and its interplay with inflammatory mediators in vitiligo pathogenesis are underexplored. This study investigates CUL3, NRF2, and the associated regulatory networks in vitiligo, integrating clinical profiling and computational docking to identify therapeutic targets. Methods: A case-control study compared non-segmental vitiligo patients with age-/sex-matched controls. Lesional skin biopsies were analyzed by qRT-PCR for the expression of CUL3, NRF2, miRNA-146a, FOXP3, NF-κB, IL-6, TNF-α, and P53. Molecular docking was used to evaluate vitexin’s binding affinity to Keap1, validated by root mean square deviation (RMSD) calculations. Results: Patients with vitiligo exhibited significant downregulation of CUL3 (0.27 ± 0.03 vs. 1 ± 0.58; p = 0.013), NRF2 (0.37 ± 0.26 vs. 1 ± 0.8; p = 0.001), and FOXP3 (0.09 ± 0.2 vs. 1 ± 0.3; p = 0.001), alongside the upregulation of miRNA-146a (4.7 ± 1.9 vs. 1 ± 0.8; p = 0.001), NF-κB (4.7 ± 1.9 vs. 1 ± 0.5; p = 0.001), IL-6 (2.8 ± 1.5 vs. 1 ± 0.4; p = 0.001), and TNF-α (2.2 ± 1.1 vs. 1 ± 0.3; p = 0.001). P53 showed no differential expression (p > 0.05). Docking revealed a strong binding of vitexin to Keap1 (RMSD: 0.23 Å), mirroring the binding of the control ligand CDDO-Im. Conclusions: Dysregulation of the CUL3/Keap1/NRF2 axis and elevated miRNA-146a levels correlate with vitiligo progression, suggesting a role for oxidative stress and immune imbalance. Vitexin’s high-affinity docking to Keap1 positions it as a potential modulator of the NRF2 pathway, offering novel therapeutic avenues. This study highlights the translational potential of targeting the ubiquitin–proteasome and antioxidant pathways in the management of vitiligo.